Water adsorption and rheological properties of full-fat and low-fat cocoa-based confectionery coatings - Meza, Barbara Erica del Valle (2018)
Growth in consumer demand for healthier and/or reduced calorie foods often brings with it the requirement to match the performance of existing products. Cocoa-based coatings are widely used in food manufacturing and low-fat formulations need to meet performance targets in terms of water adsorption (for storage), rheology (for coating), and taste. Low-fat coatings containing 3, 6 or 9% w/w vegetable oil or microparticulate whey protein as fat replacer were studied alongside a full-fat fluid as control. Equilibrium moisture contents of dried films were measured at 25 °C and gave similar adsorption behaviour which could be modelled using the Guggenheim–Anderson–de Boer model. The fat replacer increased the viscosity of the coating fluids and all the formulations exhibited Quemada model behaviour, so that the thickness of layers obtained by dip coating could be predicted by a previously reported mechanistic mathematical model. The model gave good agreement with measured layer thicknesses, indicating that the model could be used to optimise a coating film. One full-fat and one low-fat formulation with identical coating capacities were subjected to sensory analysis testing by untrained consumers and the low-fat product was found to be acceptable.